2019
DOI: 10.24200/squjs.vol24iss1pp23-35
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Acidic, Basic and Hydrophobic Dehydrated Carbons and their Capability for Methylene Blue Adsorption

Abstract: Dehydrated carbon (DC) was prepared from date palm leaflets via sulfuric acid treatment. DC was functionalized via amide coupling using ethylene diamine (EDA) and propylene diamine (PDA) to produce basic dehydrated carbons (BDCs): BDC-EDA and BDC-PDA, respectively, and using ethylamine (EA) and aniline (AN) to produce hydrophobic dehydrated carbons (HDCs): HDC-EA and HDC-AN, respectively. Surface  areas were found low, between 6.7-16 m2/g with mesoporosity domination. FTIR shows that –COOH content on DC almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In previous studies activated carbon prepared from pepper stems showed an adsorption capacity of 174 mg/g with the best performance at pH 8.0 [18] and activated carbon prepared from date palm leaves using KOH activation showed 270 mg/g, while after ethylamine functionalization the capacity increased to 393 mg/g with best performance at pH 7 [19]. Dehydrated carbon at pH 7 had a capacity of 196 mg/g, and after functionalization using ethylamine showed 296 mg/g [20]. Other adsorbents have also been used including clay [21], zeolite [22], bentonite [6], and biosorbents [23].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In previous studies activated carbon prepared from pepper stems showed an adsorption capacity of 174 mg/g with the best performance at pH 8.0 [18] and activated carbon prepared from date palm leaves using KOH activation showed 270 mg/g, while after ethylamine functionalization the capacity increased to 393 mg/g with best performance at pH 7 [19]. Dehydrated carbon at pH 7 had a capacity of 196 mg/g, and after functionalization using ethylamine showed 296 mg/g [20]. Other adsorbents have also been used including clay [21], zeolite [22], bentonite [6], and biosorbents [23].…”
Section: Introductionmentioning
confidence: 86%
“…For AC, prepared by phosphoric acid activation from coconut shell, MB capacity was 200 mg/g [37]. Other adsorbents showed different capacities including AC prepared by potassium hydroxide activation (270 mg/g) [19], dehydrated carbon (196.1 mg/g) [20], ethylamine hydrophobic activated carbon (393 m 2 /g), lignin (34 mg/g) [38], D-fructose (83 mg/g) [39], and anaerobic activated sludge (91 mg/g) [40]…”
Section: R S = 1/(1+bc O )mentioning
confidence: 99%